2013
DOI: 10.4236/psych.2013.43a054
|View full text |Cite
|
Sign up to set email alerts
|

Intellectually Disabled Victims of Sexual Abuse in the Criminal Justice System

Abstract: People with intellectual disabilities face an exceptionally high risk of being victims of sexual abuse and thereby becoming involved in the criminal justice system. Coping effectively with this system is enough of a challenge for those without disability, but it is far more difficult for the intellectually disabled. As a result, greater attention needs to be paid to their needs. From the opposite perspective, dealing with people with intellectual disabilities is a challenge for experts in forensic and criminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Surveys of offenders revealed that they select victims according to their lack of confidence as an easy target (Conte et al, 1989; Elliott et al, 1995; Niehaus et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Surveys of offenders revealed that they select victims according to their lack of confidence as an easy target (Conte et al, 1989; Elliott et al, 1995; Niehaus et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Children with intellectual disabilities can have difficulties in communication both in routine, adverse and emergency situations. Individuals with intellectual disabilities are more vulnerable due to personal and family risk factors, which leads to an imbalance of power between them and their environment that increase their probability of becoming a victim of sexual abuse (Niehaus et al, 2013). Their limited cognitive capacity reduces the ability to appropriately interpret danger signals, for example, when they are intoxicated (Tyler et al, 1998) and their low self-esteem makes it harder to set limits and successfully fending off violence (Niehaus et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations